EPIGRAPHY OF THE "TTATTI-PIR" CEMETERY (VICINITY OF THE VILLAGE BARSHAMAY) OF THE 14TH-15TH CENTURIES - Musaev, Mahac Abdulaevic; Sihaliev, Samil' Sihalievic; Sehmagomedov, Magomed Gadzievic (History, Archeology and Ethnography of the Caucasus, 2018)
A cemetery named "Ttatti-Pir" has been found one kilometer to the south-east of the village of Barshamay in the Kaytagsky district. In total it consists of 6 graves each of which is a commemorative tomb-group consisting of a box-shaped tombstone and an adjacent vertical stela set at the grave head. This is not quite usual for the region, where, as a rule, gravestones are not two- but one-part monuments. The horizontal box and vertical stela-like monuments are made of stone, have strict geometric shape, carefully processed, richly and skilfully ornamented, and bear a lot of embossed inscriptions. By the forms of tombstones and their external characteristics, compositional solutions in their decoration, ornamentation, content and calligraphic features of inscriptions, grave memorial groups can be classified into two types. The first one clearly dates back to 1370-1380. The monuments of the second type can be dated by an interval between the second half of the 14th - the very beginning of the 15th centuries. One grave memorial group mainly differs from all the other monuments in ornament and calligraphy and dates to 877 H. (1472/73). As a result of the study of the Ttatti-Pir cemetery, interesting historical information became known about a dynasty of emirs in Kaitag, who were actively engaged in religious and political activities. Two emirs fell martyrs for their faith (shahids) and one of them in a war against "polytheists" (mushriks). Further study of these monuments from the art-history point of view as well as consideration of the inscriptions in the historical context, will significantly enrich our understanding the history of the region in the 14th-15th centuries.
Keywords: Daghestan; Khaydaq; Kaytag; Muslim epigraphy; Necropolistics; Islamic art